REDISCOVERY OF THE HALMAHERA KEELBACK, Tropidonophis punctiventris (BOETTGER. 1895) (SERPENTES: COLUBRIDAE) AFTER 116 YEARS - Dadang Rahadian Subasli (Masyarakat Zoologi Indonesia, 2019)
Halmahera Keelback, Tropidonophis punctiventris is endemic to the island of Halmahera, Indonesia. The species was previously described in 1895 based on a single specimens collected in 1866 from Halmahera island. The second and third specimen was determined based on the specimens collected in 1875 and 1894 from the same island. After 116 years, the fourth specimen was collected from Kao Rahai, Halmahera. Here we provide data on morphological of the Halmahera Keelback based on the fresh collection. We discuss the rarity finding of this snake species on Halmahera, which is possibly due to the small population, hidden behavior, or the lack of intensive research in the area. These discoveries continue to underscore the fact that Halmahera is still harbour unrealized herpetological diversity, further research is needed.